Women and leadership in the news media 2021: evidence from 12 markets - Robertson, CT; Selva, M; Nielsen, RK (Reuters Institute for the Study of Journalism, 2021)
In this Reuters Institute factsheet, we analyse the gender breakdown of top editors in a strategic sample of 240 major online and offline news outlets in twelve different markets across five continents. Building off work started in 2020, we find in 2021 that only 22% of the 181 top editors across the 240 brands covered are women. In 2020, this percentage was 23% across the 200 brands covered. We find that men make up the majority of top editors eleven out of twelve markets and that while there is a positive correlation between the percentage of women working in journalism and the percentage in top editorial positions, there remains unequal representation. We also find large variation in the number of people who get news from outlets with a female top editor, along with no meaningful correlation between greater gender equality in society and the percentage of female top editors. Findings indicate no clear overall trend towards greater gender equality in top editorial positions from 2020 to 2021.